Effectiveness of epidural steroid injections in managing lumbar radicular pain: A prospective study - Bhagat SIngh,; Bharath Vadivelkumar,; Prem Kumar Kothimbakkam,; Vijayashankar Murugesan,; Thirumal Ranganathan, (Asian Journal of Medical Sciences, 2025)
Background: Lumbar radicular pain, often caused by intervertebral disc herniation or lumbar spinal stenosis, significantly affects quality of life due to nerve root inflammation and compression. Conservative treatments, including epidural steroid injections (ESIs), are commonly used to reduce inflammation, relieve pain, and improve function before considering surgery. Aims and Objectives: To evaluate the clinical effectiveness of ESIs in reducing symptoms of lumbar radicular pain, with a primary focus on functional outcomes over a 1-year follow-up period. To assess the degree of pain relief and functional improvements in patients with lumbar radiculopathy and to compare these outcomes with previous studies. Materials and Methods: A cohort of 50 patients aged 20–60 years (mean age: 41.1 years) with lumbar radiculopathy due to intervertebral disc herniation or lumbar canal narrowing was studied. Baseline assessments included routine blood work, lumbar spine X-rays (anteroposterior and lateral views), and comprehensive magnetic resonance imaging scans. Pre-anesthetic clearance was performed before ESI procedures. Data collection was standardized using a structured proforma for patient histories and lumbar spine examinations. Follow-up assessments utilized various evaluation tools over 1 year. Statistical analyses were conducted to evaluate patient outcomes and compare them with historical data. Results: During the 1-year follow-up, 86% of patients reported significant improvement and satisfaction with ESI outcomes. However, 14% of patients required surgical intervention due to persistent symptoms. Conclusion: ESIs are an effective initial treatment option for patients with lumbar radiculopathy resulting from intervertebral disc herniation or lumbar canal narrowing. The study demonstrates meaningful functional improvements and pain relief in the majority of patients, supporting ESIs as a valuable non-surgical intervention in clinical practice.